POLA KOMUNIKASI KELUARGA DAN KEPERCAYAAN DIRI (STUDI KASUS PENGARUH POLA KOMUNIKASI ORANGTUA TERHADAP KEPERCAYAAN DIRI MAHASISWA ILMU KOMUNIKASI UNIVERSITAS PGRI RONGGOLAWE TUBAN) - Shintya Agustina Wardani; Kholid Kholid (Universitas Islam Darul Ulum Lamongan, 2022)
This study is a quantitative study that aims to determine the effect of parental communication patterns on student self-confidence. The subjects in this study were Communication Studies students, PGRI Ronggolawe University, Tuban. Data collection methods used are questionnaires and documentation. The results of this study indicate that there is a significant effect of parental communication patterns on self-confidence. It can be seen from the results of the Hypothesis Test which shows that the significance value is 0.48 (<0.05), which means that H_1 is accepted and H_0 is rejected. With the direction of the relationship between the variable x and the variable y showing a positive ridge sign for the variable x and variable y.